1980
DOI: 10.1080/00222895.1980.10735224
|View full text |Cite
|
Sign up to set email alerts
|

Target-Size Influences on Reaction Time with Movement Time Controlled

Abstract: The variable that affect motor programming time may be studied by changing the nature of the response and measuring the subsequent changes in reaction time (RT). One notion of motor programming suggests that aiming responses with reduced target size and/or increased target amplitude require more "complex" motor programs that require longer RTs. In a series of five experiments which movement time (MT) was experimentally varied target size neither influences RT when the movement amplitude was 2 or 30 cm nor when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Klapp & Erwin (1976) found that RT was influenced by response duration such that an MT of 150, 300 and 600 ms produced RTs of 344, 382 and 442ms respectively, although increasing MT to 1200ms resulted in no further increase in RT (443ms). Rosenbaum & Patashnik (1980) and Quinn et al (1980) replicated the essence of this finding. These findings have led to the hypothesis that there is a fixed relationship between movement duration and reaction time (see Klapp 1996 for a review).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Klapp & Erwin (1976) found that RT was influenced by response duration such that an MT of 150, 300 and 600 ms produced RTs of 344, 382 and 442ms respectively, although increasing MT to 1200ms resulted in no further increase in RT (443ms). Rosenbaum & Patashnik (1980) and Quinn et al (1980) replicated the essence of this finding. These findings have led to the hypothesis that there is a fixed relationship between movement duration and reaction time (see Klapp 1996 for a review).…”
Section: Introductionmentioning
confidence: 81%
“…Christina 1992;Fischman 1984;Klapp & Erwin 1976;Rosenbaum & Patashnik 1980;Quinn et al 1980;Klapp 1996;Khan et al 2006).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Quinn, Schmidt, Zelaznik, Hawkins, and McFarquhar (1980) noted that response duration and required accuracy were confounded in previous studies of target aiming (e.g., Klapp, 1975). They reported that accuracy did not influence choice RT if duration was controlled, but that duration influenced choice RT if required accuracy was controlled.…”
Section: Resultsmentioning
confidence: 95%
“…By now there is a considerable amount of evidence showing that responses of longer duration tend to be associated with longer reaction times. This evidence comes mainly from key presses (e.g., Klapp, Wyatt, & Lingo, 1974;Klapp & Rodriguez, 1982) and fast aiming movements (Klapp & Greim, 1979;Quinn, Schmidt, Zelaznik, Hawkins, & McFarquhar, 1980). At least in fast aiming movements, velocity seems to be the relevant variable instead of duration (Falkenberg & Newell, 1980).…”
Section: Response Effects On Reaction Timementioning
confidence: 95%